Powinności w perspektywie pojęć niedookreślonych. Ujęcie administracyjnoprawne - Jaśkowska, Małgorzata (Kwartalnik Prawa Publicznego, 2016)
The purpose of the article is to show the obligations of both the authorities and other parties to the administrative law relationship in case of applying indeterminate terms set by the legislator. The author stresses the axiological aspect of applying the law by indicating cases of proper use of such legislative technique, as well as its abuse.